PREFERENCE AND PARTICIPATION GENERATION Z IN URBAN TOURISM EXPERIENCE - Marintan br Gurning, Linda Rotua; Rahmanita, Myrza; Ingkadijaya, Rahmat; Husain Habibie, Fachrul (Yayasan Education and Social Center, 2024)
This study aims to analyze the characteristics of Generation Z in terms of their preferences and participation in urban tourism experiences. The study uses a qualitative methodology with a design thinking approach, involving interviews with Generation Z and the DKI Jakarta Tourism and Creative Economy Agency and Focus Group Discussions (FGD) with tourism stakeholders. In addition, this study includes observation and data collection related to urban tourism, including exploration of tourist destinations, analysis of consumer behavior (especially Generation Z), and strategies for maintaining the sustainability of tourist destinations in the urban area of ​​DKI Jakarta. The author examines the behavior of Generation Z in the context of tourism, preferences for information media, and their level of involvement. Observations of tourism stakeholders were conducted to understand the vision and mission of the DKI Jakarta Tourism and Creative Economy Agency, strategies for increasing tourism attractiveness for Generation Z, and challenges faced in dealing with consumers from the digital generation. The research questions focused on Generation Z's preferences and participation in urban tourism experiences. The study results show that Generation Z is highly interested in urban tourist destinations, with social media significantly promoting and introducing tourism. In addition, innovation and application of technology are needed to increase the attractiveness of urban tourist destinations, especially for Generation Z. By leveraging innovative technologies such as Augmented Reality (AR) and gamification, the DKI Jakarta Tourism and Creative Economy Agency (Disparekraf DKI Jakarta) can effectively engage.